Wilderness gentrification et projets de rewilding - Marie Méténier (VertigO)
D.Smith et al. (2018) have recently suggested to apply the concept of wilderness gentrification in England and called researchers to pursue field research to test this hypothesis. This article aims to answer that suggestion and wishes to analyse the relevance of the wilderness gentrification concept in England’s National Parks. At difference stages of the process the wilderness appears essential for new inhabitants. It is one of the main reasons which explains their migration to the Dartmoor National Park, regarded by some to be the last wilderness in England. Therefore, considering their socio-economic profiles, their investment in the place suggests that they impulse dynamics of gentrification. Moreover, when greentrifiers transcribe their representations into practice, it appears that they tend to promote rewilding approaches at different scales. However, in Dartmoor, rewilding practices create new tensions between different social groups, especially with hill farmers. Within the Brexit context, rewilding seems to be taken seriously by the national park authorities as a new tool for nature conservation.